PENGARUH RETURN ON ASSET (ROA), DEBT TO EQUITY RATIO (DER), DAN PRICE EARNINGS RATIO (PER) TERHADAP NILAI PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI - Syah Fitri; Hamida Sari Siregar (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study was conducted to test the variables of the Influence of Return On Asset (ROA), Debt To Equity Ratio (DER) and Price Earning Ratio (PER) on the Value of Property and Real Estate sector companies listed on the IDX. With a sample of 11 companies, 3 years 2022-2024 with a total of 33 observations, quantitative research methods and using multiple linear regression. The results of the partial t-test of the Return On Asset variable have a significant effect on company value with a calculated t value> t table (7.119> 2.04227) and a significance value (0.000 <0.05), while the Debt To Equity Ratio has a significant effect on company value with a calculated t value> t table (6.705> 2.04227) and a significance value (0.000 <0.05), and the Price Earning Ratio does not have a significant effect on Company Value with a calculated t value <t table ( 1.788 < 2.04227) and significance value (0.84 > 0.05). The results of the simultaneous F test of the variables Return On Asset, Debt To Equity Ratio and Price Earning Ratio significantly influence the Company Value. producing a calculated F value> Ftable (25.013> 2.93) and a significance value (0.000 < 0.05). R2 test, the adjusted R Square value or coefficient of determination is 0.692 or 69.2%, meaning that the ability of the variables Return On Asset, Debt To Equity Ratio and Price Earning Ratio in explaining the Company Value is classified as strong, namely 69.2%, while the remaining 30.8% is explained by other factors outside the regression model. Keywords: Return On Asset (ROA), Debt To Equity Ratio (DER), Price Earning Ratio (PER), Dan Company Value   Abstrak: Penelitian ini dilakukan untuk menguji variabel Pengaruh Return On Asset (ROA), Debt To Equity Ratio (DER) dan Price Earning Ratio (PER) terhadap Nilai perusahaan sektor Properti dan Real Estate yang terdaftar di BEI. Dengan jumlah sampel 11 perusahaan, 3 tahun 2022-2024 dengan jumlah 33 pengamatan, Metode penelitian kuantitaif serta menggunakan regresi linear berganda. Hasil Uji t  secara parsial variabel Return On Asset berpengaruh signifikansi terhadap nilai perusahaan dengan nilai thitung > ttabel ( 7,119 > 2,04227 ) dan nilai signifikansi ( 0,000 < 0,05 ), sedangkan Debt To Equity Ratio berpengaruh signifikansi terhadap nilai perusahaan dengan nilai thitung > ttabel ( 6,705 > 2,04227 ) dan nilai    signifikansi ( 0,000 < 0,05 ), dan Price Earning Ratio tidak berpengaruh signifikan terhadap Nilai Perusahaan dengan nilai thitung < ttabel ( 1,788 < 2,04227 ) dan nilai signifikansi ( 0,84 > 0,05). Hasil Uji F secara simultan variabel Return On Asset, Debt To Equity Ratio dan Price Earning Ratio berpengaruh secara signifikansi terhadap Nilai Perusahaan. Menghasilkan nilai Fhitung >Ftabel (25.013 > 2,93) dan nilai signifikansi (0,000 < 0,05).Uji R2, nilai adjusted R Square atau koefisien determinasi 0,692 atau 69,2% artinya kemampuan variabel Return On Asset, Debt To Equity Ratio dan Price Earning Ratio dalam menjelaskan Nilai Perusahaan tergolong kuat yaitu 69,2% sedangkan sisanya 30,8% dijelaskan oleh faktor lain diluar model regresi. Kata Kunci: Return On Asset (ROA), Debt To Equity Ratio (DER), Price Earning Ratio (PER), Dan Nilai Perusahaan